1992
DOI: 10.1007/bf00036086
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of adult-plant resistance to Phytophthora capsici in pepper

Abstract: Inheritance studies were conducted to determine the genetic basis of adult-plant resistance in pepper (Capsicum annuum L.) to Phytophthora capsici . F1, backcrosses and F2 populations were developed using the resistant parent Criollo de Morellos 334 and susceptible parents Agronomico 10-G and Yolo Wonder . Pepper plants, at 36 days post-emergence, were inoculated near the base of the stem with an inoculum suspension of 5 X 104 zoospores/ml . Segregation ratios in the F2 generation of 13 resistant to 3 suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 12 publications
0
31
0
4
Order By: Relevance
“…Several studies have been conducted to screen resistant lines from Capsicum genetic resources, and some lines resistant to P. capsici have been found (Barksdale et al 1984, Ortega et al 1992, Reifschneider et al 1992. From these resistant resources, a local cultivar from Morelos in Mexico, 'Criollo de Morelos 334' ('CM334'), was reported to be highly resistant to P. capsici (Ortega et al 1991, Walker and Bosland 1999, Oelke et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to screen resistant lines from Capsicum genetic resources, and some lines resistant to P. capsici have been found (Barksdale et al 1984, Ortega et al 1992, Reifschneider et al 1992. From these resistant resources, a local cultivar from Morelos in Mexico, 'Criollo de Morelos 334' ('CM334'), was reported to be highly resistant to P. capsici (Ortega et al 1991, Walker and Bosland 1999, Oelke et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Some pepper accessions have been reported to be resistant to P. capsici (Smith et al 1967, Palloix et al 1990, Bartual et al 1991, Reifschneider et al 1992. In particular, two wild accessions of C. annuum, 'AC2258' derived from PI 201234 from Central America and 'Criollo de Morelos 334' ('CM334') from Mexico display a high level of resistance to P. capsici.…”
Section: Introductionmentioning
confidence: 99%
“…SCAR OpD04.717 linked to QTL Phyto 5.2 which confers resistance to P. capsici (Quirin et al, 2005) was found that the genotype SCM334 resistant to P. capsici (check), which is the pepper that has greater resistance this phytopathogen (Guerrero-Moreno and Laborde, 1980;Bosland and Lindsey, 1991;Reifschneider et al, 1992;Quirin et al, 2005;Kim et al, 2008). However, in the 142 accessions was not found, therefore it was not possible to discriminate between the accessions with possibility of having resistance or susceptibility (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…El SCAR OpD04.717 ligado el QTL Phyto 5.2 que confiere resistencia a P. capsici (Quirin et al, 2005) se encontró en el genotipo resistente a P. capsici SCM334 (testigo resistente), el cual es el chile que mayor resistencia presenta a este fitopatógeno (Guerrero-Moreno y Laborde, 1980;Bosland y Lindsey, 1991;Reifschneider et al, 1992;Quirin et al, 2005;Kim et al, 2008). Sin embargo, no se encontró en las 142 accesiones, por lo tanto no fue posible discriminar entre las accesiones con posibilidad de poseer resistencia o susceptibilidad (Figura 1).…”
Section: Resultados Y Discusiónunclassified